Pengawasan Orang Tua Terhadap Aktivitas Anak Menggunakan Media Internet Di SMA Lab School Unsyiah - NURHASANAH; Martunis; Novin Asril Lubis; Ghanda Arsenda (Majelis Pendidikan Aceh, 2023)
Parents have a big role in providing supervision to foster positive attitudes and behaviors in children's lives, including using internet media. The purpose of this study was to find out the description of parental supervision on children's using internet activities in Unsyiah Laboratory High School. This study uses a quantitative approach with a descriptive type of research. The total population is 405 students. The sample is the students totaling 61 students with random sampling technique. Data collection techniques using a questionnaire. The results of research parental supervision on children's activities in using internet media at SMA Lab School Unsyiah as a whole in the high category with a percentage of 54.1%. In terms of aspects of parental supervision, namely directing is also in the high category with a percentage of 72.1%, followed by setting 65.6% in the medium category, and guiding 59% dominantly. It can be concluded that parental supervision is high on children's activities using internet media at the Unsyiah High School Lab School in the high category.